2019
DOI: 10.1161/jaha.119.012007
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Salinity, Urinary Macro‐Mineral Excretions, and Blood Pressure in the Southwest Coastal Population of Bangladesh

Abstract: Background Sodium (Na + ) in saline water may increase blood pressure ( BP ), but potassium (K + ), calcium (Ca 2+ ), and magnesium (Mg 2+ ) may lower BP . We assessed the association between drinking water salinity and population BP . Methods and Results We pooled 6487 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…One of the other possibilities includes the presence of blood pressure-lowering minerals (e.g., potassium, magnesium) in the brackish water. In other analyses reported elsewhere [14], we identified that drinking brackish water is associated with not only a high intake of sodium but also higher intakes of magnesium, calcium, and potassium. We identified that urinary magnesium and calcium were associated with lower blood pressure, whereas urine sodium was associated with higher blood pressure.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…One of the other possibilities includes the presence of blood pressure-lowering minerals (e.g., potassium, magnesium) in the brackish water. In other analyses reported elsewhere [14], we identified that drinking brackish water is associated with not only a high intake of sodium but also higher intakes of magnesium, calcium, and potassium. We identified that urinary magnesium and calcium were associated with lower blood pressure, whereas urine sodium was associated with higher blood pressure.…”
Section: Discussionsupporting
confidence: 68%
“…Informed written consent was obtained from all participants. The studies were predominantly implemented in southwest coastal Bangladesh where communities are exposed to brackish drinking water [14]. In total, we pooled 10,031 person-visits data.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Other interventions being explored to address salinity include pond sand filter systems, managed aquifer recharge (MAR), solar-powered desalination plants, and reverse osmosis methods (Shammi et al 2019). Another potential area for exploration for blood pressure, specifically, is described in a recent study that found water with higher levels of calcium and magnesium were linked with lower blood pressure even if sodium levels were high (Naser et al 2019. Low cost, accessible, and dependable safe drinking water solutions must be evaluated and deployed in the region.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that women drinking water with high EC had higher intake of salubrious essential minerals that have been transferred to the fetus before birth or through breast milk during the nursing period. A study in coastal Bangladesh found drinking mild‐saline water was associated with higher urinary concentrations of calcium, magnesium, and sodium compared to freshwater drinkers (Naser et al, ). Magnesium in groundwater was associated with lower blood pressure of the Bangladeshi population (Naser et al, ).…”
Section: Discussionmentioning
confidence: 99%